Computational fluid dynamics - Subramanian, Raja (Anuradha Publications, 2011)
This book presents the theory and programming in the computational fluid dynamics (CFD). The theoretical discussions in CFD are presented. The programs in the visual basic language and the C-language are developed to show the practical application of the procedures in CFD